Empowering Learning Community Through Educational Technology Engagement Initiative to Strengthen The Teachers' Literacy and Numeracy Competency - Sufyadi, Susanti; Utama, Agus Hadi; Qomario, Qomario; Rini, Sulistyo; Salim, Agus (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Based on the 2023 education report card data, 76 elementary and junior high school levels in Banjarmasin still need to strengthen literacy and numeracy competencies. In order to support the improvement of the quality of education, especially in Banjarmasin, through educational technology outreach and involvement initiatives, the Educational Technology Study Program carries out community learning assistance activities to strengthen literacy and numeracy. Assistance is carried out with an inquiry cycle consisting of 4 stages: reflection, planning, implementation, and evaluation. The reflection stage produces notes on efforts to improve student's literacy and numeracy competencies that have been implemented. Then, at the planning stage, a strategy is prepared to improve literacy and numeracy competencies with a focus on understanding literacy concepts, multimodal texts, literacy-rich environments, strengthening literacy in learning, understanding numeracy concepts, developing a growing mindset, numeracy discussions, and numeracy strengthening practices in learning. At the implementation stage, educational units implement the strategies that have been prepared. At the evaluation stage, the strategies that have been completed are re-evaluated and followed up on in the subsequent learning community activities. This inquiry cycle is implemented to ensure the quality of learning and improve teacher competency sustainably. By comparing reflection data before and after participating in mentoring, it is known that there has been an increase in teacher understanding of the concept of learning communities increasing from 16% to 96.5%, for the implementation of literacy strengthening from 9.5% to 84%, and numeracy from 14.75% to 83%. In general, the average increase was 74.4%; from these data, it can be concluded that the learning community mentoring strategy implemented has an impact on improving the literacy and numeracy competencies of Elementary School teachers.